Water security assessment framework for deltas of the transboundary river basins - T.H. Truong; L.T.T. Nguyen; D.D. Nguyen; T. Pham; T.M. Vu; P.H. Nguyen; Q.T. Nguyen (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Water security for food production in the deltas of international river basins has become the top concern of the basin countries. Numerous efforts were made to develop frameworks for the assessment of water security at different scales. However, no framework could be directly applied to the deltas of the transboundary basins because they have not fully addressed the characteristics of the deltas. This study aims to develop a comprehensive framework for the assessment of water security for the international river basin deltas and applied it to the Vietnamese Mekong Delta.METHODS: The water security assessment framework was developed on the basis of the concept of water security defined by the United Nations Water following the “Driving forces-Pressure-State-Impact-Response” approach. The developed framework is then used to evaluate the water security conditions for 22 subregions of the Mekong Delta.FINDINGS: The proposed water security assessment framework comprises the following six dimensions: water resources, domestic water supply, water for economic development, water-related disasters, ecological and environmental protection, and water governance, which contain 21 indicators and 5 sub-indicators. The results of applying this framework to the Mekong Delta showed that the overall water security conditions in most subregions in 2018 were only at the medium level. The degree of water security in flood season is higher than that in the dry season. The main reasons that lead to the medium-level water security of the region have been identified, including high dependence on external water resources (more than 90%) and transboundary water cooperation between the basin countries and rather low water productivity in economic sectors. The study suggests that improvement in transboundary water cooperation and water productivity would help enhance future water security in the Mekong Delta.CONCLUSION: Assessment of the water security for the deltas of the transboundary river basins requires a comprehensive assessment framework. The framework developed in this study was successfully applied to the case of the Vietnamese Mekong Delta. The proposed framework will help policymakers of the Mekong riparian countries to monitor the impact of the basin development plans and policies on water security conditions jointly and determine appropriate solutions to enhance water security for the basin.